Hādhihi Mufāwaḍāt al-muʼtamar al-munʻaqidah bi-al-Astānah fī al-Masʼalah al-Sharqīyah sanah 1293 wa-1294 - Tūnisī, Murdakhāy Shamlah ([publisher not identified], 1878)
Report of negotiations between the Ottoman Empire, Germany, Austria, Russia, France, England, and Italy over the Balkan crisis of 1875-1876.